2019
DOI: 10.1002/sce.21524
|View full text |Cite
|
Sign up to set email alerts
|

Ninth‐grade students' perceptions of the factors that led them to major in high school science, technology, engineering, and mathematics disciplines

Abstract: On completing middle-school (ninth grade), Israeli students must choose which discipline(s) to major in upon entering high school. This study, grounded in Expectancy-Value Theory (EVT), identified and modeled the factors that contributed to students' academic choices from their own subjective perspectives. We collected qualitative and quantitative data from ninth graders in two urban middle-schools (n=295) at the school year's end. We found that (a) most students cited interest and utility value as their main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 114 publications
2
34
0
4
Order By: Relevance
“…Framed in expectancy-value models, this research explained the influencing factors and the mechanism of science career expectations from the perspective of science beliefs. First, science interest belief, self-efficacy belief, value belief and parents support could positively predict students' science career expectations, which was consistent with many studies (Mujtabaet al, 2018;Andersen & Ward, 2014;Caspi et al, 2019;Dewitt et al, 2013). Besides, the direct effect of teachers' support on science career expectations was not significant.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Framed in expectancy-value models, this research explained the influencing factors and the mechanism of science career expectations from the perspective of science beliefs. First, science interest belief, self-efficacy belief, value belief and parents support could positively predict students' science career expectations, which was consistent with many studies (Mujtabaet al, 2018;Andersen & Ward, 2014;Caspi et al, 2019;Dewitt et al, 2013). Besides, the direct effect of teachers' support on science career expectations was not significant.…”
Section: Discussionsupporting
confidence: 86%
“…On the one hand, according to the result of direct effect, students' expectation of science careers is largely influenced by their beliefs of interest, self-efficacy, value and parents' support towards science. This result showed that the factors related to students' personality and family background were the closest factors influencing their science career expectations, and the previous studies, such as Sha et al (2016), Caspi et al (2019) and Mohtar et al (2019), did not distinguish the distance effect of the influencing factors. Sha et al (2016) found that parents' INFLUENCING FACTORS OF 10 th GRADE STUDENTS' SCIENCE CAREER EXPECTATIONS: A STRUCTURAL EQUATION MODEL (pp.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…EVT has been used widely in science education research to understand the relationship between students' motivational science beliefs and key science outcomes (e.g., Andersen & Chen, 2016;Andersen & Ward, 2014;DeBacker & Nelson, 1999;Guo, Marsh, Parker, Morin, & Dicke, 2017;Sullins, Hernandez, Fuller, & Tashiro, 1995;Wang & Degol, 2013). Similar research has been conducted in other STEM areas (e.g., Ball, Huang, Cotten, & Rikard, 2017; Ball, Huang, Rikard, & Cotten, 2019;Caspi et al, 2019;Gaspard et al, 2019;Gottlieb, 2018;Lauermann et al, 2017;Perez, Wormington, et al, 2019;Riegle-Crumb et al, 2011). Researchers theorize that EVT is shaped by a mix of psychological, contextual, cultural, and social factors (Eccles, 2009;Eccles et al, 1983), and therefore individual choices are assumed to be embedded in and reflect the social and cultural forces of the individuals' environments (Wigfield & Cambria, 2010).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…f) Intentions, interests and beliefs: twenty-four studies investigated students' intentions to study physics, as well as their interests and subjective beliefs (self-concept and self-efficacy) towards learning physics content. Studies evaluating students' intentions showed that boys were more likely to study non-compulsory physics at high school or university (Caspi et al, 2019;Sheldrake et al, 2017). However, one study showed that female undergraduate students who have had intention to study physics while at high school were more likely than males to graduate with a physics degree (Rodriguez et al, 2016).…”
Section: Gender Differencesmentioning
confidence: 99%